F.L.O.S matrics for urban public transport quality services - Ismail N.; Ariffin I.B.; Aqeel S.L.; Yusoff Y.M. (American Institute of Physics Inc., 2023)
Nowadays, people are more interested in using their own vehicles rather than using public transport provided in their area. Public transport should become the main transport in urban and rural area. This is because the service provided does not meet the satisfaction level or need of customers. A survey using questionnaire was done in finding the Level of Services provided. This was conducted towards 460 passengers that covered three types of public transport modes offered in Putrajaya Central which is public bus, ERL and taxi. This is also to know the customer satisfaction and expectation in accordance to the mode provided. The main purpose of this study was to create a framework that will be used by the organization to monitor and identify when an action to be taken. At the same time, the effect of what will happen when the services provided are weak will be detected and not at its optimum level. 2018 Author(s).